2022
DOI: 10.15644/asc56/2/4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to New Dentures and 5 Years of Clinical Use: A Comparison between Complete Denture and Mini-implant Mandibular Overdenture Patients based on Oral Health-Related Quality of Life (OHRQoL) and Orofacial Esthetics

Abstract: Objective of work It is unclear how long patients need to adapt to new dentures. This study assessed adaptation and five years of clinical use, comparing complete denture wearers (CDs) and mini-implant mandibular overdenture wearers opposing a maxillary CD (MDI-OD), based on oral health reported quality of life (OHRQoL) and orofacial esthetics (OES). Material and Methods A total of 36 subjects in the CD group (25 females) and 30 subjects in the MDI group (20 females) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…In completely edentulous patients with a reduced alveolar ridge width, the insertion of four mini-dental implants (MDI) for mandibular overdenture (OD) retention and support is the alternative option to the insertion of two standard-sized implants [1][2][3][4][5][6][7][8][9][10][11]. Bone augmentation can be avoided by the insertion of narrow implants, which shortens the duration of treatment, providing a less traumatic surgical protocol [1][2][3][4][5]. Narrow dental implants (NDIs) are divided into three categories depending on their diameters: Category 3 (>3.3 mm-3.5 mm wide), Category 2 (>2.5 mm-<3.3 mm), and Category 1 (≤2.5 mm wide) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In completely edentulous patients with a reduced alveolar ridge width, the insertion of four mini-dental implants (MDI) for mandibular overdenture (OD) retention and support is the alternative option to the insertion of two standard-sized implants [1][2][3][4][5][6][7][8][9][10][11]. Bone augmentation can be avoided by the insertion of narrow implants, which shortens the duration of treatment, providing a less traumatic surgical protocol [1][2][3][4][5]. Narrow dental implants (NDIs) are divided into three categories depending on their diameters: Category 3 (>3.3 mm-3.5 mm wide), Category 2 (>2.5 mm-<3.3 mm), and Category 1 (≤2.5 mm wide) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Narrow implants are usually made of Ti90Al6V4 alloy, which has better mechanical properties than pure titanium. The insertion of four MDIs made of Ti90Al6V4 alloy in the mandible has been approved as a successful treatment option for the retention of a mandibular OD in many prospective clinical studies [1][2][3][4][5][6][7][8][9][10][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Mini-implants (MDIs) are one-piece implants and belong to the first and the narrowest category (category 1) of narrow diameter implants (diameter ≤ 2.5 mm) [ 15 ]. The MDIs have been approved as a suitable treatment option for retention of mandibular complete overdentures in subjects with narrow ridges in many follow-up studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. A recent study recommended MDIs even for the support of crowns or small bridges in the mandibular incisor region [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The four-MDI model represented the reference model, since four single-unit MDIs have been recommended to be placed interforaminally by a manufacturer. Furthermore, the insertion of four MDIs made of Ti90Al6V4 alloy in the intraforaminal region of the mandible, with rubber O-rings in metal housings for OD retention, has been a successful treatment option over a longer period of clinical observation [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The strains in peri-implant bone and the strains from distal edentulous areas under denture saddles are important factors predicting the long-term success of implants which support an OD, especially when knowing that a decrease in implant diameter may increase the stress transferred to the bone–implant interface [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, the placement of four MDIs (Grade 5, Ti90Al6V4 alloy) in the intraforaminal region has proven to be a successful treatment option for the retention and support of mandibular overdentures (ODs). Most clinical studies reported survival rates ranging from 95 to 100%, small amounts of peri-implant bone loss, and increased patients’ satisfaction [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A recent study found out that even only three MDIs can be sufficient for satisfactory five-year clinical outcomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%